Optimalisasi Strategi Pengendalian Bercak Daun Curvularia sp. pada Pembibitan Kelapa Sawit di Desa Binanga - Munawir Sajali Harahap; Emmi Juwita Siregar; Mustopa Husein Lubis; Ali Hamdani Harahap; Januardi Rosyidi Lubis; Tar Muhammad Raja Gunung (Jurnal Masyarakat Indonesia (Jumas), 2024)
The leaf staining disease caused by the fungus Curvularia sp. is a serious threat to palm coconut cultivation in Binanga Village. Surveys showed that the intensity of the attack reached 25-75% of the infected leaves, especially in seedlings aged <4 months. Humid environmental conditions, poor sanitation, and the use of infected seeds/seeds play a role in the spread of disease. Integrated control strategies combining healthy seeds/seedlings, environmental sanitation, alternate application of fungicides (azoxystrobin, mankozeb, chlorotalonil), insecticides (deltametrin, imidakloprid), and Gandasil D have proven effective. Implementing this strategy reduces the intensity of attacks by 80% and increases the percentage of healthy seedlings by 85%. Despite resource constraints, optimization of control strategies is carried out to the maximum extent possible. Strict monitoring, preventive measures, and planting of resistant varieties also play an important role. This research provides practical recommendations for increasing the production of high-quality palm coconut seedling sustainably in Binanga Village by implementing integrated control strategies against leaf spotted disease Curvularia sp.